Integrated Study on Reviewing Decision Making Process and Management Information System - Siew Poh Phung, Dr.; Valliappan Raju, Assoc. Prof. Dr.; Mohammed Nazeh, Dr. (International Journal of Engineering and Technology, 2019)
The role of Management Information Systems (MIS) is depicted and dissected in light of its capacity for basic leadership. Basic leadership process and its effect on top dimension the board in a business association is clarified with an accentuation on mechanised basic leadership. Restrictions and difficulties of MIS are talked about and an arrangement of six proposals proposed for expanding the adequacy of MIS in the basic leadership process.Â Â